2019
DOI: 10.3390/foods9010028
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antioxidant, Anti-α-Amylase, Anti-Inflammatory and Antinociceptive Water-Soluble Polysaccharides from the Aerial Part of Nitraria retusa

Abstract: In this paper, water-soluble polysaccharides (named as NRLP) were extracted from Nitraria retusa leaves. The main structural features of NRLP were determined by High-pressure size exclusion chromatography, Fourier transform infrared and Gas Chromatography/Mass Spectrometry-Electronic Impact analysis. The in vitro and in vivo biological potential of NRLP were evaluated by measuring its antioxidant (•OH and DPPH• scavenging, total antioxidant capacity), anti-α-amylase as well as anti-inflammatory and antinocicep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Characteristic bands of polysaccharides were attributed between 527 and 3351 cm −1 . The intense peak at 3351.04 cm −1 corresponded to O-H stretching vibration from polysaccharide and water whereas the signal attributed at 2929.26 cm −1 was assigned to aliphatic bending groups (C-H) [41]. The vibration of carboxylate groups (C=O) were also observed at 1636.30 cm −1 [42].…”
Section: Biochemical Characterizationmentioning
confidence: 98%
“…Characteristic bands of polysaccharides were attributed between 527 and 3351 cm −1 . The intense peak at 3351.04 cm −1 corresponded to O-H stretching vibration from polysaccharide and water whereas the signal attributed at 2929.26 cm −1 was assigned to aliphatic bending groups (C-H) [41]. The vibration of carboxylate groups (C=O) were also observed at 1636.30 cm −1 [42].…”
Section: Biochemical Characterizationmentioning
confidence: 98%
“…The attractive feature of electron‐transfer classification is that the color of the oxidant changes upon reduction using an antioxidant (Getachew & Chun, 2017). Previous studies have suggested that the antioxidant activity of the polysaccharides can be attributed to their hydrogen‐donating abilities (Rjeibi et al., 2019). The half‐maximal inhibitory concentration (IC 50 ) is an important indicator for evaluating oxidation resistance.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, a water-soluble polysaccharide isolated from Sedum dendroideum exhibited anti-inammation activity through reducing IL-1b and TNF-a production. 39 Another study also found that the alkali-soluble polysaccharide from purple sweet potato signicantly restrained pro-inammatory agents while enhancing anti-inammatory mediators. 40 These results indicated that WPSPP-1 had potential in vivo anti-inammatory activity.…”
Section: 4mentioning
confidence: 96%